Profile of the Use of Mathematics Learning Media for Strengthening Numerical Learning in Senior High Schools in Kendari City - La Misu; Salim Salim; Hendra Nelva Saputra (STAI Hubbulwathan Duri, 2023)
The purpose of this study is to describe the profile of the use of mathematics learning media to strengthen numeracy learning in senior high schools in Kendari City. This type of research is exploratory with a qualitative approach. The subjects of this study were high school mathematics teachers in Kendari City. Data collection techniques in this study using interview techniques. The data analysis technique follows the Miles, Huberman, and Saldana analysis model, which consists of three activities that coincide: data compaction, data presentation, and concluding/verification. Based on the research results and discussion, it can be concluded that the learning media used by teachers in learning mathematics still uses PowerPoint media, textbooks, zoom applications, and WhatsApp. Package books and power points are still the primary media for learning mathematics. There are no android-based mathematics learning media used by teachers. The provision of practice questions and evaluation of learning related to algebraic material, data and uncertainty, as well as geometry, is first given an initial test, and then an increase in the level of difficulty of the exercises is carried out. Students' numeracy skills are still very low because the learning process has not yet been implemented to support students' numeracy abilities. Students' numeracy skills are only facilitated by solving problems such as fractions. Numerical ability has not been associated with the problems students usually face daily.